The theology of liberalism political philosophy and the justice of God - Nelson, Eric, 1977- (The Belknap Press of Harvard University Press, 2019)
We think of modern liberalism as the novel product of a world reinvented on a secular basis after 1945. In The Theology of Liberalism, one of the country's most important political theorists argues that we could hardly be more wrong. Eric Nelson contends that the tradition of liberal political philosophy founded by John Rawls is, however unwittingly, the product of ancient theological debates about justice and evil. Once we understand this, he suggests, we can recognize the deep incoherence of various forms of liberal political philosophy that have emerged in Rawls's wake.--